Health inequalities related to psychosocial working conditions in Europe - Insa Backhaus; Krisztina Gero; Nico Dragano; Clare Bambra (European Trade Union Institute (ETUI), 2023)
This report presents results on psychosocial working conditions and health inequalities using data from the 2010 and 2015 European Working Conditions Surveys and the second wave of the 2020 Living, Working and Covid-19 survey. In brief, mean WHO-5 mental health scores declined between 2010 and 2020, indicating an increase in symptoms of depression during the pandemic. Regarding psychosocial working conditions, we found that the prevalence of job insecurity was slightly lower in the 2020 survey compared with 2010, while the prevalence of temporary contracts increased during the same period. We also found that the percentage of employees feeling that they do not have enough time to get their work done, working in their free time, worrying about work outside of working hours and experiencing work-life conflicts increased over time. Comparisons over time must be interpreted with caution, however, because of the different sampling methods of the studies included here. Educational level appears to be a prominent factor associated with intersectional inequalities in mental health at work, both before and during the Covid-19 pandemic. Across psychosocial working conditions, primarily young women (18-35 years of age) with a primary education presented worse mental health outcomes than their male counterparts or employees with a higher level of education, in general.
Keywords: 330; Arbeitsbedingungen; Psychische Krankheit; EU-Staaten